CRISPR Technology in Gene-Editing-Based Detection and Treatment of SARS-CoV-2 - Shademan, Behrouz; Nourazarian, Alireza; Hajazimian, Saba; Isazadeh, Alireza; Biray Avci, Cigir; Oskouee, Mahin Ahangar (Frontiers in Molecular Biosciences, 2022)
Outbreak and rapid spread of coronavirus disease (COVID-19) caused by coronavirus acute respiratory syndrome (SARS-CoV-2) caused severe acute respiratory syndrome (SARS-CoV-2) that started in Wuhan, and has become a global problem because of the high rate of human-to-human transmission and severe respiratory infections. Because of high prevalence of SARS-CoV-2, which threatens many people worldwide, rapid diagnosis and simple treatment are needed. Genome editing is a nucleic acid-based approach to altering the genome by artificially changes in genetic information and induce irreversible changes in the function of target gene. Clustered, regularly interspaced short palindromic repeats (CRISPR/Cas) could be a practical and straightforward approach to this disease. CRISPR/Cas system contains Cas protein, which is controlled by a small RNA molecule to create a double-stranded DNA gap. Evidence suggested that CRISPR/Cas was also usable for diagnosis and treatment of SARS-CoV-2 infection. In this review study, we discoursed on application of CRISPR technology in detection and treatment of SARS-CoV-2 infection. Another aspect of this study was to introduce potential future problems in use of CRISPR/Cas technology.